A pair of enantiomeric 5-oxabicyclic[4.3.0]lactam derivatives and one new polyketide from the marine-derived fungus Penicillium griseofulvum. Issue 19 (2nd October 2018) - Yang, Jian-Kun; Zhang, Bin; Gao, Tong; Yang, Meng-Yue; Zhao, Guo-Zheng; Zhu, Hua-Jie; Liu, Li; Cao, Fei
Abstract: A pair of enantiomeric 4-oxabicyclic[4.3.0]lactam derivatives, (+)- and (−)-penicilactam A (1 ), and one new polyketide derivative penicitrinone F (2 ) were isolated from the marine-derived fungus Penicillium griseofulvum GT-10. Their structures and absolute configurations were elucidated through extensive spectroscopic analyses combined with the calculated ECD spectra. Penicitrinone F (2 ) had moderate inhibitory activity towards Bacillus subtilis with a MIC value of 6.3 μM. Abstract :